MEDIUM SHIFT AND EXISTENCE OF ORNAMENTS ON PELINGGIH OF SACRED BUILDINGS (TEMPLES) DUE TO THE VOLCANIC IMPACT OF MOUNT AGUNG - Sumantra, I Made; Susanto, Moh. Rusnoto; Setem, I Wayan; Dewi, Citra Samara; Selimanorita, Shafa’; Dewobroto, Bambang Trisilo (Yayasan Education and Social Center, 2023)
The study of the existence of ornaments on the pelinggih (temple) buildings that utilise the black stone material of Mount Agung is considered to be only a tiny part of the ornamental manifestations applied to the black stone pelinggih building of Mount Agung when compared to the application of pelinggih ornaments using solid stone materials in general. It is done as an economic production that needs to be sold to the public, especially for Hindus in Bali. To explore this, the researcher uses socio-cultural and aesthetic approaches. The presentation of this article aims to describe (1) The form of the pelinggih temple building that has been used in the community as a place of worship. (2) The existence of ornaments, which are applied to the parts of the pelinggih building, according to the existing parts, such as the feet, the body and the top. (3) Factors influencing the creation of pelinggih with black stone material of Mount Agung, featuring ornaments with minimalist patterns. It is hoped that this research can also be used as a basis for future research to find solutions in developing techniques for sculpting or carving ornaments that utilise the black stone material of Mount Agung, using modern tools. The research approach used was descriptive qualitative. Data were collected through field surveys, literature studies, observations and interviews. Data can be collected, processed, classified and reduced, then analysed using textual and contextual analysis and interpretation. Descriptive qualitative research method that describes situations or events to make a description systematically, factually, and accurately about the facts and the characteristics of the population or sample of a particular area (Suryabrata, 2005: 76). Data in verbal form is often contained in different words with the same meaning and long and wide sentences. In conclusion, the description of ornaments on pelinggih (temple) buildings that use the black stone material of Mount Agung is related to the dominant factors that influence the embodiment of decorations. Although the structure and form of the pelinggih in the preparation have followed the ethics or the existing rules, the application of ornaments in detail is minimal, only in the form of basic patterns, both at the bottom feet, body or middle and head or top. There is still a lack of reliable and professional Gunung Agung black stone carvers